2016
DOI: 10.1590/0001-3765201620150302
|View full text |Cite
|
Sign up to set email alerts
|

The effects of coconut oil supplementation on the body composition and lipid profile of rats submitted to physical exercise

Abstract: This study aims to verify the effects of coconut oil supplementation (COS) in the body composition and lipid profi le of rats submitted to physical exercise. The animals (n=6 per group) were randomly assigned to: G1=Sedentary and Non-supplemented (Control Group), G2=Sedentary and Supplemented, G3=Exercised and Non-supplemented and G4=Exercised and Supplemented. The COS protocol used was 3 mL/Kg of body mass by gavage for 28 days. The physical exercise was the vertical jumping training for 28 days. It was deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
(18 reference statements)
1
6
0
2
Order By: Relevance
“…[11,31] In this work, the ingestion of a diet enriched with mainly saturated fats (coconut oil), containing a fat percentage ten times higher than that of the standard diet, did not cause per se an increase in the amount of energy ingested or significant variations in body weight (compared with controls fed the SD diet) during the period studied. This fact is consistent with previous data [32] and might be explained in part by the presence of lauric acid, which has been found to decrease food intake. [33,34] These results, however, contrast with the effects elicited by high-carbohydrate or cafeteria diets [35] containing comparable proportions of energy derived from lipids, which have been reported to markedly increase weight, especially that of adipose tissue.…”
Section: Discussionsupporting
confidence: 94%
“…[11,31] In this work, the ingestion of a diet enriched with mainly saturated fats (coconut oil), containing a fat percentage ten times higher than that of the standard diet, did not cause per se an increase in the amount of energy ingested or significant variations in body weight (compared with controls fed the SD diet) during the period studied. This fact is consistent with previous data [32] and might be explained in part by the presence of lauric acid, which has been found to decrease food intake. [33,34] These results, however, contrast with the effects elicited by high-carbohydrate or cafeteria diets [35] containing comparable proportions of energy derived from lipids, which have been reported to markedly increase weight, especially that of adipose tissue.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, we demonstrated for the first time that combination of regular exercise and CAPs intake significantly reduced the levels of muscle SREBP-1c, LXRs, ACLY, and FAS transcriptional regulators that induce key lipogenic enzymes to promote lipogenesis. Similarly, previous studies have shown that physical exercise has a better lipidic profile compared to sedentary ones such as higher HDL-c and lower LDL-c and VLDL-c, and capsaicinoid consumption also positively affects the expression of lipogenic genes in adipose tissue [ 34 , 38 , 63 ]. Nevertheless, it has been reported that liver mRNA expression of FAS decreased and the expression levels of hormone-sensitive triglyceride lipase increased by capsaicin and paprika seed oil in rats [ 64 ].…”
Section: Discussionmentioning
confidence: 75%
“…Additionally, young adults that consume CO do not experience a change in total plasma antioxidant capacity following a bout of moderate-intensity cycling exercise [15] Likewise, it was found in rats that CO supplementation, with or without exercise, enhanced blood triacylglycerol and VLDL-c concentrations [31]. Therefore, lipid supplements did not seem to be a healthy option.…”
Section: Discussionmentioning
confidence: 99%